Dynamic Behaviors of a Competitive System with Beddington-DeAngelis Functional Response - Shengbin Yu; Fengde Chen (Discrete Dynamics in Nature and Society)
This article studies a competitive system with Beddington-DeAngelis functional response and establishes sufficient conditions on permanence, partial extinction, and the existence of a unique almost periodic solution for the system. The results supplement and generalize the main conclusions in recent literature. Numerical simulations have been presented to validate the analytical results.